Blood Characteristics in Dogs During Treatment of Babesiosis Using Transfusion of Cryopreserved Erythrocytes - Denysova Оlha; Zhegunov, Gennadiy; Yakimenko , Tatyana; Hladka, Nataliia; Prichodchenko, Vita; Bobrutska, Olha (Problems of Cryobiology and Cryomedicine, 2021)
Babesiosis is one of the most common protozoan diseases in dogs, which in the absence of the necessary veterinary care often leads to the animal death. The changes of hematological parameters in dogs during complex treatment of babesiosis and transfusion of cryopreserved erythrocytes were evaluated in the research. Erythrocytes were frozen using 20% DMSO by immersion into liquid nitrogen. Transfusion of cryopreserved erythrocytes together with antiparasitic chemotherapy has been shown to promote rapid recovery of hematological parameters of animal blood (hemoglobin, hematocrit and erythrocyte counts), as well as improves their well-being, promotes faster recovery. Cryopreserved with DMSO erythrocytes can be recommended for long-term storage of blood at cryobanks. Probl Cryobiol Cryomed 2021; 31(4): 304–315